The Biblioteca Interseccional De Imágenes Uruguayas creation process - Ferreiro Xavier de Mello, María Eugenia (2025)
This article discusses methodological aspects and reflections on a project that is currently being developed: The creation of the Intersectional Library of Uruguayan Images, a bank of images featuring non-hegemonic characters. One of the library’s goals is to serve as a public resource for architecture and design professionals. The research question arises from the automatic and uncritical use of corporalities and poses that conform to representations based on stereotypes and imported images. The question is far from being solved with new technologies. It includes biases and automatic assumptions that need to be made visible by focusing on the production of meaning, considering that certain sectors of society are currently excluded from all visual representation in significant spaces of public life. The study incorporates surveys and analyses of the digital platforms most commonly used by design professionals in Uruguay, considering gender, generation, rights-based, and diversity perspectives to detect and overcome the problem. The work team comprises teachers and students from the Faculty of Architecture, Design, and Urbanism of Udelar. The images for the repository are produced using participatory design methodologies, with the essential contribution of activists and social groups.